The use of star blimbing wuluh flowers to relieve cough in Children aged 1-5 years - Febri Fitriani; Rani Safitri (Indonesian Journal of Health Science, 2026)
Cough is a common symptom among children aged 1–5 years and may occur in various respiratory conditions. In the community, belimbing wuluh has traditionally been used to help relieve cough symptoms; however, its use in children requires careful consideration and should not replace appropriate medical evaluation. This study aimed to analyze differences in cough frequency before and after the administration of belimbing wuluh flower decoction in children aged 1–5 years in the working area of Puskesmas Jatiroto. This quantitative study used a pre-experimental one-group pretest–posttest design. A total of 30 respondents were selected using purposive sampling. Cough frequency was defined as the number of cough episodes observed during a 15-minute observation period. The intervention consisted of belimbing wuluh flower decoction prepared using a 1:1 ratio of flowers and water (300 g:300 ml), boiled for 5–10 minutes after reaching boiling point, and administered twice daily for 5 days according to the study procedure. Data were analyzed using a Paired Sample T-Test with a significance level of p < 0.05. The mean cough frequency decreased from 10.5 episodes at pretest to 7.2 episodes at posttest, with a statistically significant difference (p = 0.004). These findings indicate a difference in cough frequency before and after the intervention period. However, because the study did not include a control group, the observed changes cannot be attributed solely to the intervention. Further research using a stronger study design and an adequate safety evaluation is needed before clinical recommendations can be made.